(untitled) (Estudios Gerenciales, 2013)
The paper analyzes the organizational learning process experienced in the design of a new packing service for the pharmaceutical sector, using the 4I model designed by Crossan, Lane and White (1999) and its further developments. It was carried out an exploratory study using qualitative research methods. It was found evidence supporting the learning processes stated by the original model and its further developments. The interviews and focus group results suggested that organizational learning is not always a lineal process as stated by the model. Individual and group learning are parallel interacting and unfinished processes. This study contributed to adding empirical evidence to the 4I model of organizational learning and its further developments, in a manufacturing firm.